A Bibliometric Review of Time-Driven Activity-Based Costing - Yaguache-Aguilar , María Fernanda; Niñerola-Montserrat , Angels; Sánchez-Rebull , María Victoria (Journal of Ecohumanism, 2024)
Purpose: The company must be able to manage costs to achieve efficiency and maintain competitiveness. This article conducts a bibliometric review of the literature on the TDABC system to analyze its evolution and scientific contribution. Design: Descriptive, relational, and content analysis techniques were applied to expand the vision of the field and identify the objectives and motivations for using TDABC. 258 articles retrieved from Scopus, Web of Sciences, and PubMed databases. Findings: Data reveals a growth in TDABC publications after 2010, the majority have been based on case studies and implemented within healthcare and manufacturing sectors. involved 947 authors who largely represent academia, and come from countries including the USA, UK, and Australia. Scientific journals specializing in health issues, business management, and accounting were most responsive. Its objectives indicate the value of TDABC for costs determination, time identification, cost-savings, and decision-making. Finally, the most cited publications are Kaplan and Anderson (2004) and Kaplan and Porter (2011) have the theoretical bases. Originality: This review provides information to academics and practitioners for the use TDABC modern cost management tools. On the other hand, TDABC is considered an innovative methodology for its application in any market segment and integral to business management.